CSIG-28. THE HEDGEHOG GENE EXPRESSION PROGRAM REGULATES LIPID FEEDBACK MECHANISMS UNDERLYING HEDGEHOG-ASSOCIATED MEDULLOBLASTOMA. (14th November 2022) - Daggubati, Vikas; Choudhury, Abrar; Vykunta, Akshara; Saulnier, Olivier; Gardell, Zachary; Reiter, Jeremy; Taylor, Michael; Raleigh, David
Abstract: Misactivation of the Hedgehog pathway can cause cancers such as medulloblastomas, the most common malignant brain tumors in children. Hedgehog signals are transmitted through primary cilia, where Hedgehog ligands bind to Patched1 and activate Smoothened through interactions with cilia-associated sterol lipids. The gene expression programs driving cellular responses to ciliary Hedgehog signals are incompletely understood. Thus, to define Hedgehog target genes and elucidate mechanisms underlying Hedgehog-associated medulloblastomas, we performed RNA sequencing of cells after treatment with Hedgehog ligands (Shh, Dhh, Ihh), cilia-associated lipids (7b, 27-dihydroxycholesterol, 24( S ), 25-epoxycholesterol), or synthetic lipids or small molecules that activate Smoothened (20(S)-hydroxycholesterol, SAG). Nonspecific gene expression changes were identified by performing RNA sequencing (1) after treatment of CRISPR mediated Smo -/ - cells with the same Hedgehog pathway agonists, (2) after treatment with vehicle controls, or (3) after treatment with sterol lipids that are unable to activate Smoothened (7a, 27-dihydroxycholesterol). Differentially expressed genes were integrated across RNA sequencing of human medulloblastomas (n=458) or the Math1-Cre SmoM2 mouse genetic model of Hedgehog-associated medulloblastoma. Mechanistic studies validating Hedgehog target genes were performed using CRISPR interference, genetic gain-of-function, molecular biology, quantitative immunofluorescence, or cell biology approaches. RNA sequencing after treatment with Hedgehog pathway agonists identified a core gene expression program comprised of 155 genes driving lipid synthesis, metabolism, signaling, adhesion, or angiogenesis. Integration of transcriptomic datasets revealed a conserved gene expression program driving cellular responses to ciliary Hedgehog signals in human or mouse medulloblastomas, including known target genes such as Gli1 or Ptch1, and novel target genes such as Hsd11b1 or Retnla . Retnla is a regulator of sterol synthase expression, and Hsd11b1 is a sterol synthase that opposes the action of Hsd11b2, a driver and druggable dependency underlying Hedgehog-associated medulloblastoma. In support of these findings, mechanistic studies demonstrated Retnla drives expression of Hsd11b2, and showed Hsd11b1 negatively regulates the Hedgehog pathway.